Impact of avail® and jumpstart® on yield and phosphorus response of corn and winter wheat in Kansas - Ward, Nicholas Charles (Kansas State University, 2010)
The increasing price of phosphorus (P) fertilizers has created interest among producers in ways to enhance the efficiency of applied P fertilizers. Research has long focused on increasing phosphorus efficiency through the use of fertilizer placement techniques (banding, strip applications, and in furrow placement with the seed). Recently, various products have been introduced and marketed claiming to increase efficiency of applied P or increase availability of native soil P. The objective of this study was to test the use of two such widely advertised products: Avail®, a long chain, organic polymer created to reduce the fixation of fertilizer P by aluminum and calcium, and JumpStart®, a seed inoculant containing a fungus (Penicillium bailii), which is said to increase the availability of fertilizer and native soil P to plant roots through the colonization of the root system and producing organic acid exudates. This study was conducted at multiple locations across Kansas with corn (Zea mays L.) in 2008 and 2009 and winter wheat (Triticum aestivum L.) in 2009. Selected sites varied in soil test P, with a majority of the locations having a Mehlich III P test of < 20mg kg-1, where a P response would be expected. Treatments consisting of P rates from 0 to 20 kg P ha-1 with and without the addition of Avail were applied at planting. At many locations, each of the fertilizer/Avail treatments were planted with and without Jumpstart seed treatment. Plant samples were collected at early and mid-season growth stages. Harvest data consisting of grain yield, grain moisture content at harvest, test weight or bushel weight and grain P content also were collected to measure treatment response. Plant samples for both trials failed to show consistent responses to the addition of either product. Excellent corn grain yields were obtained at seven of eight site years with location averages above 12,500 kg ha-1. One location displayed a significant grain yield response to P in both 2008 and 2009. There were no significant responses to enhancement products where a response to P was seen. At two of the five wheat trials, a significant tissue P response to the addition of P was seen. At one location with very low soil test, 6 mg kg-1, P fertilization increased rate of maturity. No effect on growth or yield at either P responsive or unresponsive sites was seen in wheat due to the use of enhancement products. A series of 20 single replications sites were conducted with the JumpStart product in cooperation with County Extension Agents as a part of wheat variety demonstrations. Analysis of this data showed a significant decrease in wheat yield with the addition of JumpStart in 2009. Overall, this study showed a lower than expected frequency of response to applications of P fertilizer based on soil test and the KSU P fertilizer recommendations. It also showed no response across locations, years and crops to the use of P fertilizer enhancement products.
Keywords: Phosphorus fertilizer; Phosphorus response; Corn; Wheat; Avail; JumpStart; Agriculture, Agronomy (0285); Agriculture, Soil Science (0481)